Serial nitrogen-phosphate co-limitation controls the primary productivity in the transitional waters of northern South China Sea and the Pearl River Estuary - Liu, Yuanhao; Zhou, Xunying; Niu, Ruoyu; Yan, Rongman; Xu, Shuaishuai; Guo, Kangli; Guo, Jing; Tao, Jianchang; Wu, Sha; Hou, Shengwei (Frontiers in Microbiomes, 2025)
Nitrogen (N) and phosphorus (P) are essential nutrients for marine phytoplankton, playing a crucial role in shaping the structure of microbial communities. Nutrients in coastal seawater are influenced by multiple factors, including ocean currents, terrestrial runoff, and anthropogenic activities, leading to region-specific patterns of nutrient limitation. This study investigates nutrient limitation in the transitional waters near Sanmen Island, located at the confluence of the Pearl River Estuary (PRE) and the northern South China Sea. Using 4-hourly in situ time-series observations and nutrient addition experiments, we found that nitrogen limitation persists in this region despite its proximity to the nutrient-rich Pearl River. Urea addition significantly enhanced primary productivity, as evidenced by the increased chlorophyll a concentration and the increased relative abundance of cyanobacteria, whereas phosphate addition alone favored the growth of heterotrophic bacteria, yet limited the growth of cyanobacteria and other primary producers. Combined nitrogen-phosphorus treatments revealed serial co-limitation, where nitrogen relief shifted limitation to phosphorus. In conclusion, these findings highlight the complex nutrient dynamics in transitional coastal waters and underscore the impact of anthropogenic nutrient discharge on ecosystem productivity.